The complexity issue: is languaje really that complex? - Ney, James W. (Lenguas Modernas, 2017)
Transformational generative grammarians have maintained the belief for some time now that language is so complex that it cannot be learned. This argument, in some cases, is based on incorrect argumentation, in which it is pre-empted by the use of more adequate models of linguistic processing, including Chomsky’s own model. As a result, his argument is not valid; it does not prove what he insists that it does. When viewed from a more adequate perspective, language is not as complex as Chomsky says that it is. Besides these arguments, there is also the possibility that the Chomskyan view of language, arising out of the Aristotelian philosophical tradition, makes language appear to be excessively complex. An alternative view of language would accord well with connectionism (Parallel Distributed Processing - - PDP) which offers a model of language or psychology as a mechanism for language learning quite different from the Classical view present in Western societies from the earliest times to the present. Thus, if the transformationalist view of language is incorrect and language is not as complex as it may seem from the transformationalist viewpoint and if the connectionist view of language has a measure of truth in it, then language is, in fact, more simple – probably simple enough to be learned.